Growth performance, nutrient utilisation and digestibility by Atlantic salmon (Salmo salar L.) fed Tasmanian grown white (Lupinus albus) and narrow-leafed (L. angustifolius) lupins - Salini, MJ; Louise Adams (2014)
The aim of this study was to compare the nutritional value of Tasmanian and mainland Australian grown white ( Lupinus albus cv. Luxor and Rosetta), narrow-leafed ( L. angustifolius cv. Jindalee and Coromup) and yellow ( L. luteus cv. Pootalong) lupin kernel meals when fed to post-smolt Atlantic salmon ( Salmo salar L.). Eight experimental diets were formulated to be isoproteic and isoenergetic on a crude basis. Each diet included the different lupin kernel meals at a single inclusion of 250 g/kg and one control diet was formulated with fish meal as the main protein source. A growth assay was conducted by feeding the experimental diets to triplicate groups of salmon (90.2 ± 13.7 g, mean ± SD) for 74 d, followed by the collection of faeces by abdominal stripping methods. The fish were held in a freshwater recirculation system maintained at 15 °C and were fed twice a day a restricted ration of 1.7% body weight. The lupin kernel meals utilised in this study led to significant differences in the growth and digestibility of diets by Atlantic salmon. Growth of the fish fed the diet containing L. luteus cv. Pootalong was increased compared to the fish fed several of the other lupin varieties. However, the growth and feeding efficiency of fish fed the Tasmanian L. albus cv. Luxor diet deteriorated significantly when compared to the control fed fish ( P < 0.001). The apparent digestibility of the diets was high however some significant differences were observed. Most notable were the effects on the organic matter, nitrogen, energy, arginine and lysine that were improved by the addition of the lupin kernel meals. Linear regression modelling suggested that the growth of fish was significantly reduced in response to increasing dietary quinolizidine alkaloids clearly demonstrating the anti-nutritional effect of alkaloids on juvenile Atlantic salmon used in this study. These highly useful feed ingredients grown in different regions of Australia supported adequate growth of Atlantic salmon with the only slight exception ...